COMPARATIVE ANALYSIS OF PROGRAMMABLE DEVICES WITH ANALOG AND DIGITAL INPUTS AND OUTPUTS: COMPARATIVE ANALYSIS OF PROGRAMMABLE DEVICES WITH ANALOG AND DIGITAL INPUTS AND OUTPUTS - Petkov , Milen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the present article, single-board programmable devices suitable for control of automation processes are considered. A comparative analysis of specific models of the most common single-board computers, suitable for this purpose.